Palladium nanoparticles for the synthesis of phenanthridinones and benzo[c]chromenes via C–H activation reaction - Díaz Vázquez, Eva D.; Cuellar, Micaela A.; Heredia, Micaela D.; Barolo, Silvia M.; González Bakker, Aday; Padrón, José M.; Budén, María E.; Martín, Sandra E.; Uberman, Paula M. (2024)
Impact factor: 3.9